Investigation of the impacts of urban land use patterns on energy consumption in china - Zhao, Jie; Thinh, Nguyen Xuan; Li, Cheng (Technische Universität Dortmund, 2017)
Urban land use patterns are increasingly recognized as significant contributors to energy consumption. However, few studies have quantified the impacts of urban land use patterns on energy consumption. In this study, we analyzed the impacts of urban land use patterns on energy consumption for 20 provincial capital cities in China from 2000 to 2010. Landsat data and spatial metrics were first used to quantify the urban land use patterns, and then city-level energy consumption was estimated based on nighttime light (NTL) data and statistical provincial energy consumption data. Finally, a panel data analysis was applied to investigate the impacts of urban land use patterns on energy consumption. Our results showed that NTL data were effective for estimating energy consumption at the city level and indicated that accelerated energy consumption was caused by increases in the irregularity of urban land forms and the expansion of urban land. Moreover, significant regional differences in the impacts of urban land use patterns on energy consumptions were identified. Our results provide insights into the relationship between urban growth and energy consumption and may support effective planning towards sustainable development.
A case study of 20 provincial capital cities
Sustainability / Molecular Diversity Preservation International (MDPI);Vol.9, (8), p.1383
Keywords: urban land use pattern; energy consumption; nighttime light data; remote sensing; panel data analysis; 710; Energieverbrauch; Flächennutzung; Fernerkundung; Panelanalyse